Population pharmacokinetics of oxycodone in plasma and cerebrospinal fluid after epidural and intravenous administration. (3rd June 2019) - Lamminsalo, M.; Piirainen, P.; Kokki, H.; Knibbe, C. A. J.; Ranta, V.-P.; Välitalo, P.; Kokki, Merja
ABSTRACT: Objectives : To establish the first plasma and cerebrospinal fluid (CSF) oxycodone population pharmacokinetic (PopPK) model after epidural (EPI) and intravenous (IV) oxycodone administration. Methods : The study was conducted with 30 female subjects undergoing elective gynecological surgery with epidural analgesia. A parallel single dose of EPI oxycodone with IV placebo (EPI group; n = 18) or IV oxycodone with EPI placebo (IV group; n = 12) was administered. An epidural catheter for drug administration was placed at T12/L1 and a spinal catheter for CSF sampling at L3/4. Plasma and CSF for oxycodone analysis were frequently collected. A PopPK model was built using the NONMEM software package. Results : Plasma and CSF oxycodone concentrations were evaluated using separate central plasma and CSF compartments and separate peripheral plasma and CSF compartments. Epidural space served as a depot compartment with transfer to both the plasma and CSF central compartments. The population parameters for plasma clearance and apparent distribution volumes for central and peripheral compartments for plasma and CSF were 37.4 L/h, 90.2 L, 68.9 L, 0.035 L (fixed based on literature), and 0.039 L, respectively. Conclusion : A PopPK model was developed and found to precisely and accurately describe oxycodone time-concentration data in plasma and CSF.